Isoflurane Suppresses Hippocampal High-frequency Ripples by Differentially Modulating Pyramidal Neurons and Interneurons in Mice. (5th May 2021) - Zhao, Wenling; Zhao, Shuai; Zhu, Tao; Ou, Mengchan; Zhang, Donghang; Sun, Huaiqiang; Liu, Jin; Chen, Xiangdong; Hemmings, Hugh C.; Zhou, Cheng
Abstract : Background: Isoflurane can induce anterograde amnesia. Hippocampal ripples are high-frequency oscillatory events occurring in the local field potentials of cornu ammonis 1 involved in memory processes. The authors hypothesized that isoflurane suppresses hippocampal ripples at a subanesthetic concentration by modulating the excitability of cornu ammonis 1 neurons. Methods: The potencies of isoflurane for memory impairment and anesthesia were measured in mice. Hippocampal ripples were measured by placing recording electrodes in the cornu ammonis 1. Effects of isoflurane on the excitability of hippocampal pyramidal neurons and interneurons were measured. A simulation model of ripples based on the firing frequency of hippocampal cornu ammonis 1 neurons was used to validate the effects of isoflurane on neuronal excitability in vitro and on ripples in vivo . Results: Isoflurane at 0.5%, which did not induce loss of righting reflex, impaired hippocampus-dependent fear memory by 97.4 ± 3.1% (mean ± SD; n = 14; P < 0.001). Isoflurane at 0.5% reduced ripple amplitude (38 ± 13 vs . 42 ± 13 μV; n = 9; P = 0.003), rate (462 ± 66 vs . 538 ± 81 spikes/min; n = 9; P = 0.002) and duration (36 ± 5 vs . 48 ± 9 ms; n = 9; P < 0.001) and increased the interarrival time (78 ± 7 vs . 69 ± 6 ms; n = 9; P < 0.001) and frequency (148.2 ± 3.9 vs . 145.0 ± 2.9 Hz; n = 9; P = 0.001). Isoflurane at the same concentration depressed action potential frequency in fast-spiking interneurons while slightly enhancing action potential frequency in cornu ammonis 1 pyramidal neurons. The simulated effects of isoflurane on hippocampal ripples were comparable to recordings in vivo. Conclusions: The authors' results suggest that a subanesthetic concentration of isoflurane can suppress hippocampal ripples by differentially modulating the excitability of pyramidal neurons and interneurons, which may contribute to its amnestic action. Abstract : In mice, isoflurane at 0.5% impaired hippocampus-dependent memory processing and ripple oscillations without inducing loss of righting reflex. At the cellular level, these effects were associated with decreased fast-spiking interneuron activity and a concomitantly enhanced activity of excitatory neurons. These observations suggest that the suppression of hippocampal ripples by isoflurane via the differential modulation of principal neurons and interneurons contributes to the amnestic action of this drug. Supplemental Digital Content is available in the text.